The Effect of Total Asset Turnover and Return on Assets on Company Profit Growth (Study of Mining Companies Listed on the Indonesian Sharia Stock Index (ISSI) for the 2017-2022 Periode - Iis Rahmawati; Dinda Fali Rifan; Tulus Suryanto; Raizky Rienaldy Pramasha (LP2M IAIN Palopo, 2024)
This research aims to examine the influence of Total Asset Turnover and Return On Assets on company profit growth in mining companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2017-2022 period. The method used in this research is a quantitative approach. The sampling technique used purposive sampling with a total sample of 11 companies. The data analysis used is multiple linear regression with software analysis tools Eviews 12 . The results of this research show that the Total Asset Turnover variable does not influence Profit Growth. The Return On Asset variable influences Profit Growth. The faster the asset turnover rate, the greater the net profit generated. The higher the Return On Assets , the greater the profit generated by the company. Simultaneously shows that Total Asset Turnover and Return On Assets influence profit growth , the combination of increasing Total Asset Turnover and Return On Assets will increase profit growth significantly.